Carotid stenosis: what is the high-risk population? (Clinics, 2012)
OBJECTIVE: Prevention is the best treatment for cerebrovascular disease, which is why early diagnosis and the immediate treatment of carotid stenosis contribute significantly to reducing the incidence of stroke. Given its silent nature, 80% of stroke cases occur in asymptomatic individuals, emphasizing the importance of screening individuals with carotid stenosis and identifying high-risk groups for the disease. The aim of this study was to determine the prevalence and the most frequent risk factors for carotid stenosis. METHODS: A transversal study was conducted in the form of a stroke prevention campaign held on three nonconsecutive Saturdays. During the sessions, carotid stenosis diagnostic procedures were performed for 500 individuals aged 60 years or older who had systemic arterial hypertension and/or diabetes mellitus and/or coronary heart disease and/or a family history of stroke. RESULTS: The prevalence of carotid stenosis in the population studied was 7.4%, and the most frequent risk factors identified were mean age of 70 years, carotid bruit, peripheral obstructive arterial disease, coronary insufficiency and smoking. Independent predictive factors of carotid stenosis include the presence of carotid bruit or peripheral obstructive heart disease and/or coronary insufficiency. CONCLUSIONS: The population with peripheral obstructive heart disease and carotid bruit should undergo routine screening for carotid stenosis.